The Effect of Internet Media Utilization and Learning Motivation on Mathematical Reasoning Ability - Mohammad Nasrul; Achmad Noor Fatirul; Djoko Adi Walujo (Jurnal Mantik, 2022)
The purpose of this study was to determine the test results: (1) Knowing the differences in the use of the internet on students' mathematical reasoning abilities, (2) Knowing the differences in learning motivation on students' mathematical reasoning abilities, and (3) Knowing the interaction between internet use and learning motivation on students' mathematical reasoning abilities. This experimental research was carried out using a 2x2 factorial design. The results of the calculation show that: (a) The use of internet media can increase students' ability to understand more deeply and be inspired by actual events, (b) The use of internet media students will be more motivated to understand the content of messages that can resemble facts or actual events, and (c) ) the effect in the interaction to improve students' understanding of the subject matter between the use of learning media or students' learning motivation. Based on the results of this study, it was concluded that by using Internet Media Utilization. From the results of the analysis showed that between learning media and learning motivation both contributed jointly between learning media and learning motivation, meaning that the effect of interaction between learning media and learning motivation could increase students' ability to understand both in terms of the use of internet media and without using internet media and both students who have high motivation and those who have low motivation.